If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6.6r = -4.7r + 13.3 Reorder the terms: -6.6r = 13.3 + -4.7r Solving -6.6r = 13.3 + -4.7r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '4.7r' to each side of the equation. -6.6r + 4.7r = 13.3 + -4.7r + 4.7r Combine like terms: -6.6r + 4.7r = -1.9r -1.9r = 13.3 + -4.7r + 4.7r Combine like terms: -4.7r + 4.7r = 0.0 -1.9r = 13.3 + 0.0 -1.9r = 13.3 Divide each side by '-1.9'. r = -7 Simplifying r = -7
| 3.1(f-14)+6.7=12.9 | | 5y+12=92 | | 9x+3=(-9x-10) | | -12.3b-12.95-9.94=-7.71-11.2b | | 4(5x-7)=10x+3 | | -2.6h+10.9=-4.4h-14.84 | | (3-x)=4 | | -14.87-4.5f=-3f+13.93 | | 3x+[4(x-1)]=45 | | -5.8f-13.89=-4.3f+12.96 | | y=4a+4a | | 14h+10=11h-8h-12 | | 2-13y=-13-14y | | 13h-12h+1=20 | | 12n+24=60 | | k^2+15k-25=0 | | 19j+18=18j | | 2n-n=7 | | -p-9=7p-1 | | 3/4x7= | | 3x+x+x+3x=70.08 | | 8n-13=5n+8 | | 2u+10=-6+8u-8 | | x^2*7x=30 | | 4(s+5)=-16 | | 3x-3=13x-1-3 | | 9k^2-18k+17=0 | | 3s-1=2s-10 | | -7r+6r=-16 | | 3x+37=12-62 | | -9m=-8m-4 | | -7r+6t=-16 |